Strengthening Budgeting for Sustainable Development: Uganda’s Transition from Output-Based Budgeting to Program-Based Budgeting - Ssekitoleko, Joseph (2020)
This case study examines how the government of Uganda implemented an output-based budgeting system. Uganda began transitioning from output-based budgeting to program-based budgeting in 2013 in a bid to improve the link between budgeting and national strategic objectives. Output-based budgets were developed to reflect the relationship between funding and expected outputs. The drawbacks of Uganda’s output-based budgeting system included unclear alignment with national development plans, insecure and tedious manual processes, inadequate data access and security controls, and incompatibility with other government budgeting systems. The program-based budgeting structure allocates resources by program or functional area, in alignment with the national development plan. Performance data inform decision making, either as a direct input in budget allocation or as contextual information for budget planning. The new program-based budgeting system is now online and can be accessed remotely. It provides user and security controls, can interface with other budgeting systems, and stores historical data for future use. The rollout of the new program-based budgeting approach faced several delivery challenges, including inadequate infrastructure, as well as unstable internet and power connections, which administrators solved by using well-equipped regional centers. Capacity-building workshops for all system users run at regional centers and local governments helped resolve human resource challenges such as a mismatch in skills between the central and local governments. Nonetheless, some challenges remained unresolved, including poor internet connections and road networks that hindered access to remote areas. The new system has led to better cooperation between the Ministry of Finance, Planning, and Economic Development and other agencies, ministries, and local governments that implement budget expenditures. Additionally, the automation of functions reduces the workload of users. The new system has also aligned budgets to national strategic objectives more closely and further improved budget estimates by providing checks that required the budgeting process to be completed sequentially.
Keywords: Human Resources and Organizational Capacity; Basic Infrastructure; Coordination and Engagement